What is Colombia's Sustainable Palm Oil Program - Federación Nacional de Cultivadores de Palma de Aceite, Fedepalma (My University, 2020)
Con el apoyo del Fondo de Fomento Palmero.
Keywords: Aceite de palma; Agroindustria; Colombia; Sostenibilidad